043 Depression is associated with increased dementia risk and reduced grey matter in a fronto-insular-cerebellar network. Issue 9 (12th August 2022) - Paris, Alvar; Amirthalingam, Guru; Karania, Tasvee; Dey, Sumit; Foote, Isabelle; Bothongo, Phazha; Dobson, Ruth; Noyce, Alastair; Marshall, Charles; Waters, Sheena
Abstract : Background: Depression may be a potentially modifiable risk factor for dementia, but it is not clear whether this is due to a causal effect, or whether depressive symptoms are an early prodromal feature of Alzheimer's disease. Objectives: To investigate whether depressive symptoms are associated with an increased risk of dementia. To establish associations between depressive symptoms and structural neuroanatomy. Methods: A total of 491, 603 adults from the UK Biobank study were included. Depression and dementia diagnoses were determined using linked medical records and self-report; depression symptomatology was based on questionnaire data. Brain MRI image-derived phenotypes in 42, 471 participants were used to measure regional brain volumes. Results: The risk for incident all-cause dementia was increased in participants with depressive symptoms or a recorded depression diagnosis (all OR>2, p<0.01). After excluding those with incident dementia, depressive symptoms were associated with volume reduction in a fronto-insular-cerebellar network. Conclusion: Depression is associated with an increased risk of incident dementia. The neuroanatomical correlates of depressive symptoms do not relate to the default mode network degeneration found in prodromal Alzheimer's disease, suggesting that increased dementia risk in depression may be due to poor brain health and diminished neural reserve more broadly.